Distance and E-Learning, Social Justice, and Development: The Relevance of Capability Approaches to the Mission of Open Universities - Tait, Alan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
This article reviews the discourse of mission in large distance teaching and open universities, in order to analyse the theories of development and social justice that are claimed or may be inherent in them. It is suggested that in a number of cases the claims are unsupported or naive. The article goes on to set out the nature of Amartya Sen’s capability approach for development, and to identify its potential for reviewing distance and e-learning more widely as a contributor to development and social justice.